Vibrational discomfort and motorcycle health assessment under engine excitation. (2015) - Dalawai, Prashanth; Vyas, Nalinaksh
This paper evaluates the passenger discomfort and motorcycle health by assessing relevant ISO standards and referred literature. The human vibration standards evaluate general severity with frequency weightings while comfort contours from the referred literature evaluate subjective perceived sensitivity with frequency, amplitude, location, direction and driving posture conditions. Machinery standards and referred literature evaluate the grades, permissible vibrations and fault symptoms. Experiments are conducted on four leading brands of different category motorcycles. The engine is swept from low idle to rated speed and vibration signals at different locations on the engine and chassis are recorded. Ride comfort levels and health conditions of motorcycles are quantified and analysed. Experimental observations and gaps in the ISO and referred literature are discussed. The results indicated that an unweighted rating still holds good for these experiments at a selected speed in comparison to rating by ISO weightings and sensation magnitudes.